KONDISI SOSIAL EKONOMI MIGRAN BURUH TANI DI KELURAHAN GUNDALING I KECAMATAN BERASTAGI KABUPATEN KARO PROVINSI SUMATERA UTARA - Sitepu, Mikhael Gunanta; Ginting, Bengkel (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2022)
Indonesia as a developing country faces a problem where many people still live below the poverty line. Low levels of education, lazy to work, limited natural resources, limited employment opportunities, limited capital and others, are one of the reasons why people cannot compete for jobs and do not have the capital to improve their socio-economic conditions, causing unemployment. From the phenomena encountered in this condition, namely the emergence of migrant farm workers in several areas. The area that absorbs a lot of migrant farm workers in Kelurahan Gundaling I Kecamatan Berastagi Kabupaten Karo. This study aims to obtain an overview of the socio-economic conditions of migrant farm workers before and after migrating. In this study, the main informants of this study were three migrant farm workers who had lived for at least 5 years and had been married, the key informants were village officials, and additional informants were two land owners or service users of migrant farm workers in Kabupaten Karo. Data collection techniques were carried out by literature study, observation, interviews, and documentation. The data obtained in the field are then analyzed qualitatively to produce conclusions.